Polarization-selective electromagnetically induced transparency in asymmetric mid-infrared plasmonic metamaterials - Pham, The Linh; Anh, Nguyen Hai; Mai, Nguyen Thi; Lam, Vu Dinh; Janssens, Ewald; Tung, Nguyen Thanh (Communications in Physics, 2026)
We demonstrate polarization-controlled electromagnetically induced transparency (EIT) in asymmetric H-shaped plasmonic metamaterials operating in the mid-infrared regime (5-16 μm). Through controlled symmetry breaking of coupled gold cut-wire resonators, we achieve strong coupling between bright (superradiant) and dark (subradiant) modes, evidenced by an anti-crossing behavior in the reflectance spectrum. Fourier-transform infrared spectroscopy reveals a tunable transparency window with up to 55% reflectance suppression under TE polarization, while a single plasmonic resonance is maintained under TM-polarized excitation. Finite-integration technique simulations and field distribution analysis confirm the hybridized nature of the observed states, showing quadrupole-dipole mode interaction. The polarization-selective EIT response emerges from coupling between vertical and horizontal resonators whose coupling strength is systematically controlled via lateral displacement (0-0.2 μm) of the vertical resonator. This work establishes a robust platform for tunable mid-infrared photonics, bridging quantum-inspired phenomena with practical metamaterial design for applications in molecular sensing, active optical components, and quantum plasmonics.